2013
DOI: 10.1128/iai.01108-12
|View full text |Cite
|
Sign up to set email alerts
|

Full-Length Plasmodium falciparum Circumsporozoite Protein Administered with Long-Chain Poly(I·C) or the Toll-Like Receptor 4 Agonist Glucopyranosyl Lipid Adjuvant-Stable Emulsion Elicits Potent Antibody and CD4+T Cell Immunity and Protection in Mice

Abstract: ؉ T cell responses. Finally, protective immunity was also induced using the Toll-like receptor 4 agonist glucopyranosyl lipid adjuvantstable emulsion (GLA-SE) as the adjuvant, which also correlated with high antibody titers yet CD4 ؉ T cell immunity that was significantly less potent than that with poly(I·C)LC. Overall, these data suggest that full-length CS proteins and poly(I·C)LC or GLA-SE offer a simple vaccine formulation to be used alone or in combination with other vaccines for preventing malaria infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 70 publications
2
61
0
Order By: Relevance
“…S2D in the supplemental material). These differences in immunogenicity between EcCSP and PpCSP are in agreement with the findings presented in a previous report on CSP immunogenicity (20).…”
Section: Resultssupporting
confidence: 82%
“…S2D in the supplemental material). These differences in immunogenicity between EcCSP and PpCSP are in agreement with the findings presented in a previous report on CSP immunogenicity (20).…”
Section: Resultssupporting
confidence: 82%
“…Yet, mice immunized with P. pastoris expressed Ov -103 had a statistically significant reduction in parasite survival but not with E. coli expressed antigen; Ov -RAL-2 induced a statistically significant reduction in parasite survival only if produced by E. coli ; and Ov -CPI-2M produced in either Pichia or E. coli induced protective immunity. In other studies, no differences were observed in the immune responses induced by E. coli and Pichia expressed antigens (Giersing et al, 2005), whereas some antigens were more immunogenic if produced in E. coli compared with Pichia (Kastenmuller et al, 2013) and yet other antigens were more antigenic if produced in Pichia compared with E. coli (Yang et al, 2012). …”
Section: Discussionmentioning
confidence: 80%
“…Additionally, it is noteworthy that several mice with low repeat-specific antibody titers were protected in the present study, as is often observed with RTS,S-immunized humans. Although cellular immune responses to CSP were not measured, T-cell epitopes in the N-and C-terminal regions of CSP might have contributed to protection (6,19), as observed by others using CSP-transgenic parasite models (11,23).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports suggest that transgenic rodent parasites expressing the P. falciparum CSP gene are viable and infective in mice. One such parasite, in which the central repeat region of Plasmodium berghei CSP was exchanged with that of P. falciparum, has been used recently to evaluate the protective efficacy of P. falciparum CSP vaccines in mice (10,11). However, such parasites provide no information on the protective role of the Nand C-terminal epitopes of CSP.…”
mentioning
confidence: 99%